(untitled) (International Journal of Physiotherapy, 2018)
Background: Muscle tone in Preterm infants (PTI) is lower actively and passively compared to full-term infants (FTI) due to reduced flexor muscle tone even at term age. They show more extension and difficulty moving against gravity due to maturation-related hypotonia which may affect the motor development of the child. Birth weight and gestational age signify the level of growth of various systems at birth which might impact the motor development. This study aims to correlate the effect of birth weight, gestational age and muscle tone with the motor development of PTI at eight months of corrected age. Methods: This cross-sectional study included 39 PTI who met the criteria for eight months of corrected age. Subjects were recruited from Child Development Unit when the infant returned for developmental assessment. Birth weight and Gestational age were noted, and motor development was assessed with Peabody Developmental Motor scale (PDMS 2). Muscle tone was assessed using Amiel-Tison Angles (ATA) with a goniometer. Results: Gestational age did not show a significant correlation, but birth weight showed a positive correlation and Muscle tone assessed with ATA showed significant negative correlation with Gross Motor Quotient (GMQ), Fine motor Quotient (FMQ) and Total Motor Quotient (TMQ) of PDMS with a p-value <0.05. Conclusion: The study concludes that motor development is influenced significantly by birth weight and muscle tone and maturation-related hypotonia is found to be carried in PTI during the first year of life which has an impact on motor development. Clinicians should consider strategies to improve the muscle tone in the initial periods to prevent motor delays in these infants.